Reed, Sheila (London, 2007)
2007 "Reed, Sheila", 2007, Bishopsgate Institute Sheila Reed was born in Stepney in 1935. She entered clothes manufacturing, also known as the "rag trade", as a machinist after leaving school. She worked in the East End with many of the other local women in the rag trade. She describes why she entered the rag trade and didn't get an office job, because she felt she didn't have the appropriate education.